Automatic System for Detection and Positioning of Impacts in Metals Based on Arduino. (28th May 2019) - Morón, Carlos; Ferrández, Daniel; Saiz, Pablo; Morón, Alberto
Abstract : This work presents a new application to detect vibrations in metallic structures based on low-cost sensors compatible with the Arduino platform that enables identification of points where the impact is produced, in order to facilitate inspection. If the impact is produced on a metal bar, the energy introduced in the system is spread through the material in the form of vibration. Thus, using standardized construction steel rods B500SD that can be considered homogeneous along entire section, it was possible to detect where the impact is produced, measuring delays of propagation of acoustic wave throughout the material. For that, it was necessary to place the accelerometers at the ends of the structure that enables an automatic and efficient way to determine the moment and the position of the impact. Hypothesis of supported beam was taken into consideration, obtaining for distances of 0.1 and 0.9 m with delay times of 500  μ s.